Under pressure: suitable areas for neotropical cats within an under protected biodiversity hotspot - Ribeiro-Souza, Paula [UNESP]; Haji, Júlio [UNESP]; Oshima, Júlia [UNESP]; Lima, Fernando [UNESP]; Lima-Silva, Barbara; Pires, José; Ribeiro, Milton [UNESP]; Graipel, Maurício (Elsevier, 2024)
Understand which factors influence the distribution of feline species can contribute to better planning of conservation strategies in a biodiversity hotspot. We modeled the potential distribution of seven cat species occurring in the Atlantic Forest (AF). Here, we combined climatic and landscape perspectives to determine the most suitable areas considering the taxonomic richness of these cats. We also assessed the ability of fully protected areas (FPAS) to protect these cat species. The results indicated that only 30% of the AF remnants are suitable for all species. Areas with low species richness were located in Argentina and northeastern Brazil. For taxonomic richness, the Serra do Mar (45.89%) and the Araucaria (27.90%) sub-regions had the highest suitable areas, followed by the Interior sub-region (21.89%). The Brejos Nordestinos and Pernambuco sub-regions had less than 1% suitability. Considering taxonomic richness, only 9% of suitable areas are covered by FPAs. Leopardus emiliae (1.37%) and Panthera onca (1.97%) had the lowest values of suitable areas covered by FPAs. The other species of cats are also under low protection (L. guttulus = 5.38%, L. wiedii = 5.71%, Herpailurus yagouaroundi = 6.70%, L. pardalis = 3.85%, and Puma concolor = 4.94%). We reveal that a low percentage of suitable areas are currently fully protected. This study also provides important conservation measures to be implemented in different AF sub-regions. These findings may help in the planning, maintenance, and implementation of FPAs through restoration programs and the establishment of ecological corridors.
Keywords: Atlantic forest; Biodiversity conservation; Habitat loss; Species distribution model; Species richness